Negocjacje językowe. Tożsamość, grupy mniejszościowe i literatura - Chutnik, Sylwia (2022)
The paper presents changes in the language that is used in the definition of minority groups, especially women, nonbinaryand black people. It also analyzes the challenges faced in the translation of this literature and in that whichis written in Polish. Drawing both on official sources, such as the expertise of the Polish Language Council of thePolish Academy of Sciences, and on the bottom-up language guides developed by people belonging to minoritygroups, the situations requiring negotiation and also the search for appropriate language (new grammar, pronouns,performativity of forms) is illustrated, indicating ways to minimize the inequalities linguistic hierarchy.
Keywords: 20th and 21st century literature; minority languages; queer; feminatives; political correctness; racism